Conditional versus non-conditional incentives to maximise return of participant completed questionnaires in clinical trials: a cluster randomised study within a trial - Cook, J; Cook, JA; Bongard, E; Heneghan, C; Butler, CC (BioMed Central, 2023)
Background High participant retention enhances the validity of clinical trials. A monetary incentive can increase retention, but it is not known if when it is provided and if it is conditional matters. We aimed to determine whether there was a difference in the number of follow-up trial questionnaires returned when a monetary (gift voucher) incentive was given to participants at recruitment (non-conditional), compared to informing participants at recruitment that the incentive would be given only once their 14-day daily diary (questionnaire) had been returned (conditional).